The Influence of Filipino Culture on the Mechanization Program in Nueva Ecija, Philippines - Alcantara, Ashley Joy; Basmala, Jasmin; Sepillos, Semera Yluj; Pasquin, Eric (International Journal of Social and Management Studies, 2022)
The Philippine economy has been growing due to a service sector driven engine. The evidently changing economic landscape brought by a vibrant service industry does not hide the fact that the agricultural sector is still significantly essential that basic demands of the households are met. Despite the national accounts' strong position, the farmers who are considered as the most hardworking people remain to be the most marginalized. A major challenge faced by the farmers is modernization. This article aims to examine the influence of Filipino culture, namely, the traditional values, local agricultural practices, and family farm business succession towards the agricultural development initiative of the Department of Agriculture which is the Mechanization Program in the Province of San Isidro, Nueva Ecija. A 5-sectioned semi-structured survey questionnaire was used to assess 100 respondents. This study used purposive sampling method coupled with multiple regression analysis in assessing the influence of Filipino culture on the mechanization initiative of the national government. The study found out that the Filipino traditional values, Pagpapahalaga sa Pamilya (Familistic Orientation) and Hiya (Propriety), have a positive influence on the Farm Mechanization Program. It is identified that the dominant agricultural method is the Traditional method which also has a positive impact on the program. Lastly, Family farm business succession does not have a significant influence on the program.